Humanities and Their Impact on Sustainable Development - غانم, قصي غازي (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The concept of development is among the key notions that have received considerable attention from writers and researchers, particularly in recent times. This heightened interest becomes evident when examining the large body of articles addressing the subject, given its significance for individuals and societies across all dimensions. In the economic sphere, development plays a central role in strengthening societal economies, as it represents one of the essential pillars supporting the stability of any community. The aim of this study, which approaches the humanities in general and literature in particular, is to highlight the importance of development and the ways it is nourished through what writers and literary figures have expressed in their texts and cultural heritage. The study seeks to clarify the sound foundations of development and to identify the obstacles that hinder its realization, such as economic afflictions and political and social crises. This orientation guided the structure of the research, which focused on the causes and barriers to development—whether political, economic, or social—through a descriptive-analytical methodology. This approach involved selecting research samples, subjecting them to descriptive analysis, extracting the developmental principles embedded in literary texts, and reading them in light of the authors’ contemporary societies. The study further identifies the major obstacles to development in order to highlight points of strength that can serve as foundations for stable and well-grounded developmental progress, ultimately leading to sustainable, enduring development. The significance of the study thus becomes clear, as it demonstrates that the humanities in general, and literature in particular, play a vital role in understanding social needs, articulating them, and contributing to their enhancement and growth in ways that promote stability and sustainability.